ANALISIS LITERATUR TENTANG STIGMA SOSIAL TERHADAP PESERTA DIDIK BERKEBUTUHAN KHUSUS PENDIDIKAN DI SEKOLAH INKLUSIF - Nurmalasari, A.; Rajmi; Andi Nadya Smara; Sri Amanda; Nurhasanah; Laeli Qadrianti; Irwin Hidayat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Inclusive education reflects the state’s commitment to providing equal educational rights for all children regardless of physical oe mental conditions. However, its implementation still faces challenges, especially social stigma toward students with special needs in inclusive schools. This study aims to examine the forms, causes, impacts, and handling strategies of stigma. The method used is a literature review of recent scientific sources. The results show that stigma appears in the form of stereotypes, discrimination, and violence caused by limited disability literacy, cultural influences, and inadequate school facilities. The impacts affect students’ phychological condition, academic achievement, and social interaction. Therefore, comprehensive efforts through education, policy strengthening, and collaboration are needed to create an inclusive and discrimination-free educational environment.